Perinatal Al-Quran Sound to Novel Object Recognition Memory and Hippocampal Cell Count - Tryando Bhatara; Achadiyani Achadiyani; Uni Gamayani; Herry Herman (Universitas Islam Bandung, 2018)
Al-Quran sound as auditory stimulation may influence the development of systems related to memory. This study aimed to investigate the effect of Al-Quran acoustic stimulation to novel object recognition (NOR) memory and amount of hippocampal formation cells at postnatal day (PND) 21 Wistar rats. This study was conducted in September 2016 to January 2017. Adult Wistar rats divided into intervention and control groups were bred at Faculty of Medicine Universitas Islam Bandung. Rat pups in the intervention group were exposed to Quranic sound from postcoital day 0 to the PND 20. Rats of PND 20 was involved in the NOR test by documenting the value of the duration of exploration of the familiar and novel object. The rats’ brains were extracted and processed at Faculty of Medicine Universitas Padjadjaran for cell counting of hippocampal formation stained with hematoxylin-eosin. The results displayed a higher value of D1 (exploration time difference) and a total number of hippocampal formation cells in the Al-Quran groups. These results can be related to the role of the Quranic voice in suggesting higher learning aspects, activating neurogenesis or cell survival transcription factors. However, there was no difference in discrimination index (DI) value between groups which could be indicating inadequate habituation period, interval, testing age, or stress factors. Numerous limitations from this field of research suggest that the biological role of sound stimulation is still in its early stages of development. In conclusion, exposure to perinatal Al-Quran sound may serve as stimulation which enhances learning, memory, neurogenesis or cell survival of hippocampal formation. SUARA AL-QURAN PERINATAL PADA MEMORI NOVEL OBJECT RECOGNITION DAN JUMLAH SEL HIPOKAMPUSSuara Al-Quran sebagai stimulasi pendengaran diperkirakan dapat memengaruhi perkembangan sistem tubuh terkait memori. Penelitian ini bertujuan mengamati pengaruh stimulasi suara Al-Quran terhadap memori novel object recognition (NOR) dan jumlah sel formasi hipokampus pada tikus Wistar 21 hari setelah lahir (postnatal day/PND). Penelitian ini dilaksanakan pada September 2016 sampai Januari 2017. Tikus Wistar dewasa yang dibagi dalam kelompok perlakuan dan kontrol dibiakkan di Fakultas Kedokteran Universitas Islam Bandung. Anak tikus Wistar dipaparkan dengan suara Al-Quran sejak hari postcoital 0 sampai anak tikus lahir dan berumur 20 hari setelah lahir (PND 20). Tikus PND 20 dilibatkan dalam tes NOR dengan dokumentasi nilai durasi eksplorasi objek lama dan baru. Otak tikus diproses di Fakultas Kedokteran Universitas Padjadjaran untuk penghitungan jumlah sel formasi hipokampus dengan pewarnaan hematoxylin-eosin. Hasil penelitian ini menunjukkan nilai D1 (perbedaan durasi eksplorasi objek lama–baru) dan jumlah sel formasi hipokampus lebih tinggi pada kelompok perlakuan dengan Al-Quran. Hasil tersebut dapat terkait dengan peran suara Al-Quran dalam aktivasi faktor pertumbuhan atau transkripsi. Namun, tidak terdapat perbedaan bermakna pada nilai indeks diskriminasi antarkelompok yang dapat terkait dengan faktor stres atau kurangnya periode habituasi atau periode uji. Berbagai keterbatasan penelitian ini serta riset di bidang stimulasi embriologi mengindikasikan bahwa peran biologis suara Al-Quran masih harus diteliti lebih lanjut. Simpulan, paparan suara Al-Quran perinatal dapat berlaku sebagai stimulasi yang meningkatkan pembelajaran, memori, neurogenesis atau ketahanan sel formasi hipokampus.